Interaction between buyer power in agricultural procurement and seller power in food retailing, and optimal allocation of anti-trust efforts - Tian Xia; Brian Sancewich (Agricultural and Food Economics, 2018)
In order to take appropriate and effective actions against anticompetitive behaviors in the agricultural sector, it is essential to understand the interaction between buyer power in agricultural procurement and seller power in food retailing and the optimal allocation of anti-trust efforts between markets to maximize welfare. This paper finds that, even if the policy objective is to maximize farmer welfare, anti-trust efforts may need to put to both farm and retail markets. More importantly, the optimal allocations of anti-trust efforts are the same for three different policy objectives: to maximize farmer welfare, to maximize consumer welfare, and to maximize social welfare. The steepness of farm supply and consumer demand curve, along with processors' buyer power and retailers' seller power, can affect the optimal allocation of anti-trust efforts. Some guidelines and formula are suggested for designing optimal allocation of anti-trust efforts between farm and retail markets.
Keywords: 330